PHATIC COMMUNICATION IN THE CONTEXT OF CASUAL CONVERSATION OF SIKKA PEOPLE IN WOLOMOTONG VILLAGE - Mas, Isidorus Gulun; Sareng, Carmelita Riayanti; Lalong, Aloysius (Journal of Language and Literature, 2023)
This study aims to describe Phatic Communication in The Context of Casual Conversation of Sikka People in Wolomotong Village. This research used descriptive qualitative analysis method.  The object of this research is the phatic communication in Wolomotong Village. The result show that Phatic Communication of Sikka People in Wolomotong Village is divided into several types i.e. greeting to break the silence, joking to creating harmony and comfort, requesting, satire, and making a small talk. From the result show that type of phatic communication that is often used by the people of Wolomotong Village to interact everyday is greeting. These types respectively serve the functions of expressing solidarity, friendship and creating harmony and comfort in Wolomotong Village.